A Preliminary Investigation of Health and Work-Environment Factors on Presenteeism in the Workplace. Issue 12 (December 2018) - McGregor, Alisha; Ashbury, Fred; Caputi, Peter; Iverson, Donald
Abstract : Objective: This study investigates the health and work-environment factors that are associated with presenteeism. Method: A self-report survey that measured presenteeism, 13 health conditions (eg, stress and allergies), and nine work-environment factors (eg, job strain and leadership) was completed by 229 workers. Results: The most common health condition was stress, while the most common work-environment factor was job strain. Allergies, asthma, and high blood pressure along with work-life imbalance, poor leadership, and a lack of development opportunities were associated with presenteeism. Finally, several inter-relationships between the health and work-environment factors were also reported. Conclusion: Interventions targeted at the points of intersection among the health conditions and work-environment factors could be a cost-effective way to improve employees' overall well-being at work, and thus reduce presenteeism.